PENGARUH TINGKAT PENDIDIKAN, DISTRIBUSI PENDAPATAN, DAN PERTUMBUHAN PENDUDUK TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Winda Yanthi, Ni Putu Devi; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022, 2022)
The problem of poverty is a complex and multidimensional problem. Therefore, poverty alleviation efforts must be carried out comprehensively, covering various aspects of people's lives, and implemented in an integrated manner. This study aims to determine the effect of education level, income distribution, and population growth simultaneously and partially on poverty in the regions/cities of Bali Province, as well as the most dominant variables influencing poverty in the regions/cities of Bali Province. The analysis technique used in this study uses multiple linear regression analysis techniques. The results of this study indicate that the level of education, income distribution, and population growth have a significant effect on poverty in the regions/cities of Bali Province. Partially, the education variable and income distribution partially have a significant negative effect on poverty in the districts/cities of Bali Province, while the population growth variable partially has a significant positive effect on poverty in the regions/cities of Bali Province.